Determination of hormoligosis of organophosphate insecticides against Phenacoccus solenopsis - Yaseen,A. (2022)
Abstract Cotton mealybug is a highly invasive pest of agricultural crops worldwide. Major agriculturists most rely on the use of insecticides for the control of pesticides. So, the indiscriminate use of insecticides leads to resistance development in recent years. For this purpose, an experiment was conducted using different concentrations of the three insecticides (profenfos chlorpyrifos and triazophos) to check the hormoligosis effects against cotton mealybug (CMB) in laboratory conditions. Investigation of variations for % mortality of adults of CMB after three days revealed that all treatments had statistically significant (P ˂ 0.05). The highest mortality was observed at the highest concentrations of profenofos 2.4% (38.55%). After 7 days, all the treatments were significant with difference in means (P ˂ 0.05). The highest mortality was recorded at the highest dilution of pesticide profenofos 2.4% (77.11%). The values of fecundity and longevity exposed a valid difference among treatments (P ˂ 0.05). Maximum fecundity was observed at the concentration 2.4% (181.41%) and longevity showed (38.46%). The highest mortality was observed at a concentration of triazophos 4% (27.98%). For chlorpyriphos the highest mortality was examined at concentration 4% (24.79%). The fecundity showed a statistically significant difference for different concentrations of triazophos and chlorpyriphos (P ˂ 0.05). The results of the recent study provide valuable information regarding the selection of insecticides and hormoligosis effects. The study can be helpful in the implications of integrated pest management of P. solenopsis.